RESPONSIBILITIES OF MOBILE PHONE COUNTER BUSINESSES IN MEDAN TEMBUNG DISTRICT REGARDING EXCHANGING MOBILE PHONE SPARE PARTS PERSPECTIVE OF FATWA NUMBER 112/DSN-MUI/IX/2017 - Ratna Aprilia; Fatimah Zahara (Warmadewa Press, 2024)
This research aims to find out why business actors exchange cellphone spareparts. How responsibility of business actors in the practice of exchanging mobile phone spare parts without the customer's knowledge, review Fatwa number 112/DSN-MUI/IX2017. This research uses empirical juridical methods or also commonly called sociological juridical. The responsibility of mobile phone counter business actors regarding the exchange of mobile phone spare parts from the perspective of fatwa number 112/DSN-MUI/2017 is compensation for repairing cellphone spareparts which should not have been exchanged but were exchanged by the cellphone counter because the manufacturer tried to break the agreement at the beginning of the transaction.